Identification of Insecticidal Constituents of the Essential Oil of Acorus calamus Rhizomes against Liposcelis bostrychophila Badonnel - Shu Shan Du (Molecules, 2013)
The aim of this research was to determine the chemical composition of the essential oil of Acorus calamus rhizomes, its insecticidal activity against the booklouse, (Liposcelis bostrychophila) and to isolate any insecticidal constituents from the essential oil. The essential oil of A. calamus rhizomes was obtained by hydrodistillation and analyzed by GC-FID and GC-MS. A total of 32 components of the essential oil of A. calamus rhizomes was identified and the principal compounds in the essential oil were determined to be α-asarone (50.09%), (E)-methylisoeugenol (14.01%), and methyleugenol (8.59%), followed by β-asarone (3.51%), α-cedrene (3.09%) and camphor (2.42%). Based on bioactivity-guided fractionation, the three active constituents were isolated from the essential oil and identified as methyleugenol, (E)-methylisoeugenol and α-asarone. The essential oil exhibited contact toxicity against L. bostrychophila with an LD50 value of 100.21 µg/cm2 while three constituent compounds, α-asarone, methyleugenol, and (E)-methylisoeugenol had LD50 values of 125.73 µg/cm2, 103.22 µg/cm2 and 55.32 µg/cm2, respectively. Methyleugenol and (E)-methylisoeugenol possessed fumigant toxicity against L. bostrychophila adults with LC50 values of 92.21 μg/L air and 143.43 μg/L air, respectively, while the crude essential oil showed an LC50 value of 392.13 μg/L air. The results indicate that the essential oil of A. calamus rhizomes and its constituent compounds have potential for development into natural fumigants/insecticides for control of the booklice.